"The Influence of Different types of Secondry Scbool On the Academic Achievment of students in higher Education The case of AAU" - Tekele, G/Kidan (The Ethiopian Journal of Education, 2024)
In order to acompllsh its purpuse this study consists of four main chapters that are framed in the following sequence.